The Impact of Corporate Social Responsibility in Bangladesh Halal Food Industry - Hossain, Mohammad Faruk; Md Ismail, Che Thalbi; Mahdzir, Nazli (International Research Association for Sustainable Development, 2021)
For Muslims, all worldly deeds are equal to worship if they are performed in the way given by Allah (SWT). Every aspect of human life is recorded in the Muslim’s Holy book Al-Quran. The Muslim way of eating or trading is determined and governed by Islamic law. Allah (SWT) has ordained for Muslims all the permissible and forbidden worldly matters. The main purpose of this article is to discuss the impact of corporate social responsibility with halal food and halal food business in Bangladesh. Halal food is one of the most important elements of daily life of Muslims. This article focuses on what kind of steps a halal food business needs to take to protect the religious beliefs and obligations of Muslims. So that the supply of Bangladeshi halal food in the international market and halal quality of international consumers can be ensured